Formulation and optimization of solid dispersion of Clopidogrel with PEG 6000 - Shailendra Kumar Singh, Soukarya Som, Upender Shankhwar (Journal of Applied Pharmaceutical Science)
Clopidogrel, a non competitive inhibitor of adenosine diphosphate at the platelet receptors, is an anticoagulant drug practically insoluble in water. In order to improve the aqueous solubility of drug and its dissolution rate solid dispersions of clopidogrel were prepared with different proportions of the hydrophilic carrier PEG 6000. A two factor three level statistical design was used to quantify the influence of PEG 6000 and Clopidogrel on the dissolution profile of the solid dispersions prepared where PEG 6000 and Clopidogrel were chosen as independent variables while dissolution rate was chosen as dependent variable. Melt fusion method and solvent evaporation method were used for the preparation of solid dispersion. Results obtained showed that there was a significant increase in the dissolution rate of the drug as well as solubility of the drug in comparison to pure drug. Differential scanning calorimetry. X-ray diffraction and scanning electron microscopy analysis revealed the formation of solid dispersion of the drug with PEG 6000.
Keywords: Clopidogrel, solid dispersion, PEG 6000, Dissolution, Factorial Design